2022
DOI: 10.3390/ijms23084286
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Generation of Extra-Islet Insulin-Producing Cells in Diabetic Rats, Treated with Sodium Phthalhydrazide

Abstract: β-cells dysfunction plays an important role in the pathogenesis of type 2 diabetes (T2D), partially may be compensated by the generation of extra-islet insulin-producing cells (IPCs) in pancreatic acini and ducts. Pdx1 expression and inflammatory level are suggested to be involved in the generation of extra-islet IPCs, but the exact reasons and mechanisms of it are unclear. Macrophages are key inflammatory mediators in T2D. We studied changes in mass and characteristics of extra-islet IPCs in rats with a strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…It is likely that this mediator can be activated by inflammation. This is consistent with the previous investigations [ 17 , 35 , 52 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is likely that this mediator can be activated by inflammation. This is consistent with the previous investigations [ 17 , 35 , 52 ].…”
Section: Discussionsupporting
confidence: 94%
“…Inflammation is able to induce cell transition during regeneration [ 34 ]. Early we revealed, that at the 30 days of experimental T2D the mass of solitary IPCs in pancreatic acinar increases [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the effect of sodium aminophthalhydrazide (APH) on the generation of extra-islet insulin-producing cells (IPC) in acini and pancreatic ducts in rats with or without diabetes. The results indicated that APH modulates the functional activity of macrophages, shifting them to a reparative anti-inflammatory phenotype and decreasing macrophage infiltration and inflammation in the pancreas [11].…”
mentioning
confidence: 94%
“…Modulation of macrophage phenotypes has been suggested as a novel strategy for the treatment of inflammatory pathologies. The paper of Abidov and colleagues published in the Special Issue addressed T2D pathology with an in vivo study [11] (Figure 2G). Chronic inflammation, generated by T2D progression, increases tissue damage with the involvement of macrophage-produced mediators in both tissue injury and tissue repair.…”
mentioning
confidence: 99%
See 1 more Smart Citation